Synergistic application of biochar and lime modulates rhizosphere microbiome, suppresses pathogens, and enhances disease resistance in sugarcane - Shakeel Ahmad; Mengrong Wang; Hongming Zhang; Yaowen Deng; Qingmin Liang; Bing He; Ronghui Wen (BMC Microbiology, 2025)
Abstract Soil acidification disrupts microbial communities and exacerbates plant disease susceptibility in agriculture. This study demonstrates that combined application of biochar (15 t ha⁻¹) and lime (1.5 t ha⁻¹) in acidic sugarcane fields significantly elevates soil pH (up to 46.7%) and organic carbon (SOC), driving profound restructuring of the rhizosphere microbiome. High-throughput sequencing revealed suppression of potentially pathogenic bacteria (Solirubrobacteraceae, Acidothermus, Gaiella) and fungi (Curvularia, Scytalidium, Myrothecium), alongside qPCR-confirmed reduction in Fusarium abundance. Concurrently, we observed significant enrichment of beneficial taxa including plant-growth-promoting bacteria (Sinomonas, Bacillus, Brevibacillus, Micromonospora, Filomicrobium, OLB13, Arenimonas) and fungi (Trichoderma, Aspergillus, Talaromyces, Penicillium, Taifanglania, Redeckera). FUNGuild analysis confirmed decreased relative abundance of fungal plant pathogen guilds, particularly under the combined treatment. Redundancy analysis identified pH, SOC, and acid phosphatase as key environmental drivers of microbial assembly. These microbiome shifts correlated with enhanced plant defense responses: increased phenylalanine ammonia-lyase and superoxide dismutase activities, reduced malondialdehyde content, and significantly suppressed pokkah boeng disease incidence (82.57% reduction) and severity. Our findings establish that biochar-lime synergy ameliorates soil constraints, functionally modulates the rhizosphere microbiome to suppress pathogens, and systemically enhances plant immunity, providing a sustainable strategy for managing soil-borne diseases in acidified agroecosystems. Graphical Abstract